The effect of a novel plant activator on photosynthesis in wheat - Janse van Rensburg, Riana (University of the Free State, 2009)
The use of plant activators offers an exciting new approach for the enhancement of growth and yield in crops and ornamental plants. During a previous study, the effect of a Lupinus albus L. seed suspension (SS), a novel plant activator, was tested on different crops. Field trials indicated that SS application could be linked to improved growth and yield of agricultural as well as horticultural crops. The aim of this study was thus to confirm the results of Van der Watt (2005) by studying the effects of SS on photosynthesis and gene expression in wheat. When applied to Thatcher + Lr34 wheat, chlorophyll a fluorescence measurements indicated that unstressed plants were not dramatically affected by SS application. However, when placed under water and heat stress, SS treatment improved the actual photosynthetic ability of the plants by reducing photo-inhibition as measured by heat loss as opposed to the control treatment. On molecular level, three different techniques were used to confirm the expression of selected genes after SS treatment, with RT-qPCR analysis ultimately being the most effective. RT-qPCR confirmed the induced expression by SS of two photosynthesis related genes (RbcL and PGK), one chloroplast associated gene (Ptr ToxA BP1) and one defence gene (PR3). The expression of these genes indicated that SS is an important activator and that its main target site in wheat is related to the photosynthetic system. In this system SS improves membrane stability but also aid in the delivery of electrons across the chloroplast membrane. SS is able to induce a PR defence response that is able to protect field crops against pathogenic infection. This study thus confirmed that SS does indeed function as an effective plant activator that when applied, would benefit the plant on various different levels.
Dissertation (M.Sc. (Plant Sciences)--University of the Free State, 2009
Keywords: Growth (Plants) -- Regulation; Wheat; Plant regulators; RT-qPCR; Photosynthesis; Ptr ToxA BPI; Lupinus albus L. seed suspension; Gene expression